2023
DOI: 10.3390/bs13070526
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to Chinese Culture and Mental Health Issues among Foreign Students on Chinese University Campuses during the COVID-19 Pandemic: A Collaborative Ethnographic Study

Abstract: Foreign students in China may have difficulty adjusting to Chinese culture and may experience mental health problems related to acculturation, interpersonal issues, and social communication within the context of campus life. Therefore, this study attempts to apply a collaborative ethnography approach to explore the adjustment to Chinese culture and mental health issues among foreign students on Chinese campuses during the COVID-19 pandemic. We spent 16 months exploring the feelings and perceptions of 82 foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Yang et al [ 13 ] also pointed out that the main factors of college students’ learning adaptation include learning motivation, teaching mode, learning ability, learning attitude and environmental factors. Li et al [ 16 ] found that there existed adjustment to Chinese culture and mental health issues among foreign students on Chinese university campuses during the COVID-19 pandemic from a collaborative ethnographic study perspective. In addition, Yu et al [ 23 ] also highlighted the effects of academic adaptation on the depression of international students in China from a case study on South Asian students of a TCSOL teacher program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yang et al [ 13 ] also pointed out that the main factors of college students’ learning adaptation include learning motivation, teaching mode, learning ability, learning attitude and environmental factors. Li et al [ 16 ] found that there existed adjustment to Chinese culture and mental health issues among foreign students on Chinese university campuses during the COVID-19 pandemic from a collaborative ethnographic study perspective. In addition, Yu et al [ 23 ] also highlighted the effects of academic adaptation on the depression of international students in China from a case study on South Asian students of a TCSOL teacher program.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that the learning adaptability of international students is challenging. Cross-cultural adaptation theory in this study provides a solution to this challenge [ 11 , 16 ]. The findings show the learning adaptability of international students in China comprises seven variables: learning attitude, motivation to study abroad, learning ability, language level, learning environment, teaching management and social relations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, it should be noted that our study primarily focused on Chinese vocational undergraduates, and it is crucial to acknowledge that cultural and societal factors play a pivotal role in shaping the experience and expression of mental health issues [65,67]. Chinese culture places a strong emphasis on collectivism, social harmony, and family bonds [67]. These cultural values could significantly impact how individuals perceive and respond to NLEs and the subsequent feelings of loneliness and depression [20].…”
Section: Discussionmentioning
confidence: 99%